The Anxiety as a risk factor of endothelial dysfunction in young females during Russian-Ukrainian War - Тиравська Yuliya; Savchenko, Oleksandr; Lyzogub, Viktor; Talabko, Yuliia (Psychosomatic Medicine and General Practice, 2023)
This text is the abstract of the VI Scientific and practical conference with international participation "Psychosomatic Medicine: science and practice" which took place on November 2-3, 2023 in Kyiv on the Mediamed portal.